Commercial Chinese polyherbal preparation Zao Ren An Shen prescription for primary insomnia: a systematic review with meta-analysis and trial sequential analysis - Zhao, Fei-Yi; Xu, Peijie; Kennedy, Gerard A.; Zheng, Zhen; Zhang, Wen-Jing; Zhu, Jia-Yi; Ho, Yuen-Shan; Yue, Li-Ping; Fu, Qiang-Qiang; Conduit, Russell (Frontiers in Pharmacology, 2024)
Background: Natural products are widely used for primary insomnia (PI). This systematic review with trial sequential analysis (TSA) aimed to summarize evidence pertaining to the effectiveness and safety of Zao Ren An Shen (ZRAS) prescription, a commercial Chinese polyherbal preparation, for treating PI. Methods: Controlled clinical trials appraising ZRAS compared to controls or as an add-on treatment were systematically searched across seven databases until January 2024. Cochrane ROB 2.0 and ROBINS-I tools were adopted to determine risk of bias. Quality of evidence was assessed using the GRADE framework. Results: We analyzed 22 studies, involving 2,142 participants. The effect of ZRAS in reducing Pittsburgh Sleep Quality Index scores was found to be comparable to benzodiazepines [MD = 0.39, 95%CI (−0.12, 0.91), p = 0.13] and superior to Z-drugs [MD = −1.31, 95%CI (−2.37, −0.24), p = 0.02]. The addition of ZRAS to hypnotics more significantly reduced polysomnographically-recorded sleep onset latency [MD = −4.44 min, 95%CI (−7.98, −0.91), p = 0.01] and number of awakenings [MD = −0.89 times, 95%CI (−1.67, −0.10), p = 0.03], and increased total sleep time [MD = 40.72 min, 95%CI (25.14, 56.30), p < 0.01], with fewer adverse events than hypnotics alone. TSA validated the robustness of these quantitative synthesis results. However, the quality of evidence ranged from very low to low. The limited data available for follow-up did not support meta-synthesis. Conclusion: While ZRAS prescription shows promising effectiveness in treating PI, the overall quality of evidence is limited. Rigorously-designed randomized control trials are warranted to confirm the short-term efficacy of ZRAS and explore its medium-to-long-term efficacy. Systematic Review Registration: (https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=471497), identifier (CRD42023471497).